Dok3 restrains neutrophil production of calprotectin during TLR4 sensing of SARS-CoV-2 spike protein - Loh, Jia Tong; Teo, Joey Kay Hui; Lam, Kong-Peng (Frontiers in Immunology, 2022)
Increased neutrophils and elevated level of circulating calprotectin are hallmarks of severe COVID-19 and they contribute to the dysregulated immune responses and cytokine storm in susceptible patients. However, the precise mechanism controlling calprotectin production during SARS-CoV-2 infection remains elusive. In this study, we showed that Dok3 adaptor restrains calprotectin production by neutrophils in response to SARS-CoV-2 spike (S) protein engagement of TLR4. Dok3 recruits SHP-2 to mediate the de-phosphorylation of MyD88 at Y257, thereby attenuating downstream JAK2-STAT3 signaling and calprotectin production. Blocking of TLR4, JAK2 and STAT3 signaling could prevent excessive production of calprotectin by Dok3-/- neutrophils, revealing new targets for potential COVID-19 therapy. As S protein from SARS-CoV-2 Delta and Omicron variants can activate TLR4-driven calprotectin production in Dok3-/- neutrophils, our study suggests that targeting calprotectin production may be an effective strategy to combat severe COVID-19 manifestations associated with these emerging variants.